The other #metoos - Cheema, Iqra Shagufta (Oxford Studies in Gender and International Relations, 2023)
"To bring more awareness to the revolutionary international impact of #MeToo, The Other #MeToos brings together chapters that look at specific iterations of the #MeToo movement across multiple communities, cultures, and countries. Going beyond gender, the book takes into account the intersectional assemblage of location, history, religion, ethnicity, race, class, and neoliberal aspects that inform #MeToo and its place in local and transnational feminisms. From Egypt, Lebanon, Iran, Tunisia, and Morocco to India, Pakistan, Bangladesh, Nepal, and Sri Lanka to South Africa to Latin America to South Korea, Japan, and China to Czech Republic - #MeToo has inspired local movements and hashtag trends as well as transnational and collective hashtags like #MosqueMeToo. Therefore, by making feminism mainstream, it has rendered possible international feminist solidarities unlike any other feminist movement that precedes it. It is critical to document this defining feminist moment of #MeToo and its variants to acknowledge the diversity and multidimensionality of transnational feminisms, along with looking at the various ways they have been changed by the #MeToo, internationally. To that argument, the contributions in this collection examine, analyze, and interrogate the reception, translation, and adaptation of #MeToo in their local, indigenous, minoritized, othered, and/or postcolonial contexts. Overall, The Other #MeToos highlights the adaptation, translation, and impact of #MeToo in non-Western, postcolonial, minoritized, and othered locales to expand the larger discourse and praxes of the #MeToo movement beyond its Americentric focus to explore other feminist possibilities that the movement has enabled"--
Keywords: Feminism; MeToo movement; Sexual harassment of women